Kartikeya depicted on the external walls of the Mandapa - Temples of India Project Team (Jio Institute, 2024)
Kartikeya is depicted on the external walls of the mandapa (pillared hall). Though most of his arms are fragmented, he holds a kamandalu (water pot) in his intact hand, symbolizing purity and divinity. He is identifiable by his vahana (mount), the mayura (peacock), depicted below him.